Considering Urban Dynamics in spatial electric load forecasting - Melo, J. D. [UNESP]; Carreno, E. M.; Padilha-Feltrin, A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
When dealing with spatio-temporal simulations of load growth inside a service zone, one of the most important problems faced by a Distribution Utility is how to represent the different relationships among different areas. A new load in a certain part of the city could modify the load growth in other parts of the city, even outside of its radius of influence. These interactions are called Urban Dynamics. This work aims to discuss how to implement Urban Dynamics considerations into the spatial electric load forecasting simulations using multi-agent simulations. To explain the approach, three examples are introduced, including the effect of an attraction load, the effect of a repulsive load, and the effect of several attraction/repulsive loads at the same time when considering the natural load growth. © 2012 IEEE.
Keywords: agent; distribution planning; land use; load growth; multi-agent; spatial electric load forecasting; urban dynamic; Distribution planning; Distribution utilities; Load growth; Multi agent simulation; Natural loads; Radius of influences; Spatio-temporal simulation; Urban dynamics; Agents; Electric load forecasting; Land use; Urban growth